Structure of cocoa agroforest of Southern Cameroon - Sonwa, D.J.; Weise, Stephan F.; Nkongmeneck, B.A.; Tchatat, M.; Janssens, M.J.J. (Centro Agronómico Tropical de Investigación y Enseñanza, 2007)
This study determined the structure of cocoa plantations along a continuous gradient of market access, population density and resource use intensity in the humid forest zone of southern Cameroon. The study area comprises the sub-regions of Yaoundé, Mbalmayo, and Ebolowa. Market access, population density and resource use intensity all decreased from the first to the third sub-region. For cocoa and associated plants, we determined (i) the density; (ii) the basal area across strata; (iii) the total structure of associated plants; and (iv) the typology of agroforest based on cocoa and other trees (including Musa species and oil palms). Cocoa agroforests of southern Cameroon present a variation of structures that offer several management options for biodiversity conservation and fulfilment of other socio-economic and ecological services.